Memperbaiki Akhlak Peserta Didik Melalui Teknik Mind Mapping - Ayshah Nur Fatimah (Universitas Indraprasta PGRI Jakarta, 2020)
Morals occupy a very important position in Islam so that every aspect of Islamic teachings is always oriented towards cultivating and building noble morals. This study aims to find out how to improve morals through mind mapping technique in the counseling guidance in SMP N 1 Eromoko. This research used the qualitative method with a case study approach. The techniques of collecting data used by the researcher were observation, interview, and documentation. While the data validity technique used data triangulation and persistence of observation, the data analysis technique used a descriptive qualitative approach. The result of this study explained that improving morals through mind mapping techniques in counseling guidance in SMPN 1 Eromoko, Wonogiri in the Academic Year 2018/2019 was carried out with these following steps: greeting, testing the honesty, explaining the students’ problem, grouping students who had inadequate behavior, explaining the mind mapping, dividing groups, drawing a mind mapping based on students’ inadequate moral, focusing in the center, making branches that connected to the center, filling the branches with actions which taken to improve morals, using the keyword, color, dan picture, line which was easy to remember, then evaluating and observing.